KONTEKS UJARAN DALAM BERITA ACARA PERKARA KASUS BODY SHAMING DI PENGADILAN NEGERI MAKASSAR: TINJAUAN LINGUISTIK FORENSIK - Fajrul Khaer; Munirah Munirah; Syahruddin Syahruddin (Universitas Negeri Makassar, 2023)
The Context of Speech in the Minutes of Cases of Body Shaming at the Makassar District Court: A Forensic Linguistic Study. The purpose of this study is to describe the context of the speech and find out the existing legal review of the body shaming case at the Makassar District Court. This research is a descriptive study using the ethnographic theory of communication. The object of research is the case report. The data collection instruments in this study were the documentation method and note-taking. The data that has been identified is then broken down into SPEAKING elements, which are an acronym for building elements of the context of speech events. Furthermore, the SPEAKING elements consist of settings and scenes, participants, ends, acts, keys, instrumentals, standards, and genres. The results showed that the use of the word